Multi-Criteria Decision Making for Computer Antivirus Software using Fuzzy AHP Approach / Siti Nur Athirah Mohd Zulkifly...[et al.] - Mohd Zulkifly, Siti Nur Athirah; Mohamad, Siti Nurul Fitriah; Che Kob, Siti Aziemah; Mohd Yusof, Nurul Azilah; Mohamed, Firdawati; Aziz, Nurul Suhada; Othman, Suziana Aida (2022)
Nowadays, there are many antiviruses software developed by the information sectors to ensure the security of computer systems. As a result, consumers and information professionals are always debating whether antivirus software provides the best protection on a given criterion. However, there are various types of security software out there that can influence users’ decisions. In addition, the determination of the appropriate antivirus software can be classified as a multi-criteria decision-making (MCDM) problem. Several methods could be used to determine the multi-criteria problem such as the method of Fuzzy Analytic Hierarchy Process (FAHP), Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), and using an advanced method of Neutrosophic set. Hence, in this study, the method of Fuzzy Analytic Hierarchy Process (FAHP), one of the most powerful MCDM methods is employed for the selection of the appropriate antivirus software. Four criteria, twelve sub-criteria, and five alternatives of selection antivirus software are the main MCDM structures that need to be solved using the proposed method. A group of experts was invited to provide a rating of performance values of criteria and alternatives using a linguistic scale. The result has shown that Kaspersky Antivirus is the most preferred antivirus software that meets the criteria. This result will help users, especially computer software technicians in a certain organization to choose the preferred Antivirus to suggest to their employer. Furthermore, suggestions for further work are also provided for future study.